Aluminium alloys as structural material: A review of research. (15th January 2021) - Georgantzia, Evangelia; Gkantou, Michaela; Kamaris, George S.
Highlights: Research studies on the performance of structural aluminium alloys are discussed. Research on material and structural members are tabulated. Applicability of the international design specifications is reviewed. Recommendations for future research in this field are stated. Abstract: Over the last few decades aluminium alloys have been increasingly used in the construction sector due to their favourable properties. Thereafter, many research projects have been carried out with the aim to obtain a more comprehensive understanding of their structural performance and develop accurate and reliable design formulae. The scope of this paper is to provide a comprehensive review of research by discussing the reported experimental, numerical and analytical work on structural aluminium alloys. The paper presents an overview of research studies on the mechanical properties of aluminium alloys under monotonic, cyclic and thermal loading conditions. Moreover, a considerable amount of experimental and numerical investigations focussing on the structural performance and design of aluminium columns, beams and beam-columns is reviewed. The performance of connections and composite aluminium-concrete members is also discussed. Comments on the suitability of the international design specifications to structural aluminium alloys are included. Within the review, knowledge gaps are identified and the corresponding research work to fill these gaps is recommended.